Indian Applicant Files Patent Application for Fully Automated Dermatoglyphics Multiple Intelligence Test for Whole Brain Analysis and Development (Indian Patents News, 2015)
The abstract of the patent published by the Controller General of Patents, Designs & Trade Marks states: "The present invention provides a novel system, tool and technique for multiple-intelligence and psychometric assessment testing in subjects for developing confidence with respect to their weak and hidden talent.